When antivirals backfire: An evaluation of favipiravir's clinical outcomes in critically ill patients with COVID-19: A multicenter cohort study - Khalid Al Sulaiman; Ohoud Aljuhani; Ghazwa B. Korayem; Ali F. Altebainawi; Mashael AlFaifi; Majed Nahari; Alaa Almagthali; Abrar K. Thabit; Raghad Alhajaji; Reham Alharbi; Khawla Kahtani; Abeer A. Alenazi; et al. (Elsevier, 2023)
Background: Favipiravir is an oral antiviral, that might treat COVID-19 by enhancing viral eradication, particularly in patients with mild-to-moderate disease. Yet, the findings on the use of favipiravir in critically ill patients with COVID-19 are inconsistent. Therefore, this study aimed to assess the effectiveness and safety of favipiravir in critically ill patients with COVID-19. Method: A multicenter retrospective cohort study includes critically ill adult patients with COVID-19 admitted to the intensive care units (ICUs) was conducted from March 2020 to July 2021. Patients were categorized based on favipiravir use (control vs. favipiravir). The primary outcome was in-hospital mortality. Secondary outcomes included mechanical ventilation (MV) duration, 30-day mortality, ICU length of stay (LOS), hospital LOS, and complications during the stay. Results: After propensity score (PS) matching (1:1 ratio), 146 patients were included in the final analysis. A higher in-hospital and 30-day mortality were observed in patients receiving favipiravir compared to the control group at crude analysis (65.3% vs. 43.8%; P-value=0.009 and 56.3% vs. 40.3; P-value=0.06, respectively); however, no differences were observed using multivariable Cox proportional hazards regression analysis (HR 1.17; 95% CI 0.73, 1.87; P-value =0.51 and HR 0.86; 95% CI 0.53, 1.39; P-value=0.53, respectively). Conversely, the MV duration and ICU LOS were longer in patients who received favipiravir than the control group (β coefficient 0.51; CI 0.09, 0.92; P-value = 0.02, β coefficient 0.41; CI 0.17, 0.64; P-value = 0.0006, respectively). Complications during the stay were comparable between the two groups. Conclusion: The use of favipiravir in critically ill patients with COVID-19 did not demonstrate a reduction in mortality; instead, it was linked with longer MV duration and ICU stay. This finding suggests limiting favipiravir use to infections where it is more effective, other than COVID-19. Further randomized clinical trials are needed to confirm these findings.